DETERMINANTS OF HEALTH INSURANCE OWNERSHIP AMONG THE WORKING-AGE POPULATION IN EAST NUSA TENGGARA, 2023 - Arista Marlince Tamonob; Anugrah Jordan; Farly Oktriany Haning; Ganesha Lapenangga Putra; Maria Lobo (Universitas Airlangga, 2026)
Universal Health Coverage (UHC) aims to ensure that all individuals have equitable access to quality and affordable health services. Although coverage under Indonesia’s National Health Insurance (Jaminan Kesehatan Nasional/JKN) program has continued to increase, disparities in health insurance ownership persist, particularly in less developed regions such as East Nusa Tenggara (Nusa Tenggara Timur/NTT) Province. Health insurance coverage in NTT remained below the national UHC target in 2023, especially among the working-age population. This study aims to evaluate the achievement of UHC in NTT Province based on health insurance ownership and to analyze factors associated with health insurance ownership among the working-age population using a binary logic regression approach. The results of this study demonstrate that age, education level, self-medication, outpatient or inpatient care, savings accounts ownership, and business sector are significantly associated with health insurance ownership (? − ????? ≤ 0.05) with the Nagelkerke R Square value of 3.8%. In contrast, area of residence, gender, marital status, employment status, and health complaints were not significantly associated with health insurance ownership (? −????? > 0.05). These findings are expected to provide evidence-based input for policymakers in designing more targeted strategies, particularly those focusing on education, financial access, and employment sectors, to increase health insurance coverage among the working-age population in regions with low UHC achievement.